"To recover what has been lost": essays on eschatology, intertextuality, and reception history in honor of Dale C. Allison Jr - Ferda, Tucker S.; Frayer-Griggs, Daniel; Johnson, Nathan C. (Novum Testamentum / Supplements, 2021)
La 4e de couverture indique : "Over the course of his career, Dale Allison has enriched our understanding of Jewish and Christian hopes about the end of history, advanced nuanced readings of ancient texts in light of their scriptural and cultural conversation partners, and deepened our knowledge of the history of biblical interpretation throughout the ages. In all of these ways, he has sought, in the words of T.S. Eliot, “to recover what has been lost.” In “To Recover What Has Been Lost”: Essays on Eschatology, Intertextuality, and Reception History in Honor of Dale C. Allison Jr., leading biblical scholars and historians offer ground-breaking studies on Jewish and Christian eschatology, intertextuality, and reception history—three areas particularly evident in Allison’s scholarship. These essays reconstruct the past, advance fresh readings, and reclaim overlooked exegetical insights. In so doing, they too recover what has been lost"
Bibliogr. à la fin des chapitres. Index
Keywords: Bible; Critique et exégèse; Bible; Appréciation; Festschrift; Aufsatzsammlung; Exegese; Bibel / Neues Testament